(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article discusses issues related to the history of the activities of kazyats in Turkestan in the late XIX – early XX century, legal regulations, notarial actions, influence on local government, economic, political, social, religious, cultural life, the order of clerical work of judges of the Turkestan territory, legal foundations and legislative reflection of legal values.